Involvement of Women Village Leaders in Developing Dialogues on Forest Conflict Resolution - Titiek Kartika Hendrastiti; Pramasti Ayu Kusdinar (Jurnal Perempuan, 2019)
This article is a study of feminist ecological politics in rural women’s leadership and their involvement in resolving conflicts over protected forests. On the one hand, structurally, there is a complex linkage between social, cultural, adat, and religious practices that prevent women from becoming leaders. On the other hand, after they won the leadership contestation in the village, their task was able to go beyond reconciliation and introduce an alternative discourse on sustainable forest conservation. This study examines three main areas namely: (1) ecological sustainability knowledge, understanding and practices; (2) the practice of equal access to natural resources, and responses to vulnerability to environmental change; and (3) equality practices in village development activism. The narrative of feminist ecological political studies from two villages in Kepahiang and Rejang Lebong Districts shows that women village heads are able to penetrate structural barriers, social exclusion, and dismantle economic class barriers.